Oral Hygiene and Dentition Status in Patients with Congenital Hemorrhagic Disorders: A Comparative Study - Mathangi Kumar; Keerthilatha M. Pai; Ravindranath Vineetha; Annamma Kurien (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare the status of oral hygiene and dentition in patients with congenital hemorrhagic disorders with their age-matched healthy counterparts. Also, the prevalence of fear of dentists/ dental treatment among these patients was assessed. Material and Methods: This study was performed on children and adults with von Willebrand disease (vWD), hemophilia (A or B), and healthy subjects. Oral health and dentition status was assessed using the simplified oral hygiene index (OHI-S), plaque index, and the decayed, missing, filled teeth (dmft/DMFT) index. One-way ANOVA test was employed to compare the oral hygiene and dentition status of subjects in the three groups. A p-value of <0.05 was considered statistically significant. Results: The DMFT score did not vary significantly between the groups (p>0.05). Higher OHI-S scores and a poor oral hygiene status was observed more in the hemophilia group than the vWD group and healthy controls. A total of 27.3% of the subjects in the vWD group, 18.2% of subjects in the hemophilia group, and no subjects in the healthy group had a fear of dentists or dental treatment. Conclusion: Subjects with vWD had a higher number of carious teeth when compared to the other groups. Poor oral hygiene status was observed in subjects with hemophilia.